ANALISIS PERUBAHAN KEBIJAKAN PENDIDIKAN DARI KURIKULUM 2013 KE KURIKULUM MERDEKA - Puspita, Yanti; Atikah, Cucu (NOKEN : Jurnal Pengelolaan Pendidikan, 2023)
This curriculum emphasizes enjoyable and burden-free learning. Each learning process is expected to be differentiated to accommodate the diversity of students' interests and talents. In this study, the method used was literature research. The data collection technique involved searching for information related to the research focus through notes, books, scientific articles, and other relevant sources. The research instrument used by the researcher was a checklist of research materials based on the topics and focus of the study. This study’s findings are: 1) replacing the National Final Examination (USBN) with competency assessments for students. This assessment consists of written tests, portfolios, and group assignments such as essays; 2) eliminating the National Examination and replacing it with Minimum Competency Assessment and Character Survey developed by schools; 3) simplifying lesson plan; 4) more flexible zoning regulations for new student admission; 5) teaching assistance in educational units to provide work experience for students. In order to achieve the noble goals of the Merdeka Curriculum, support from all educational stakeholders, parents, and the community is needed. In addition, periodic training for teachers is necessary to improve readiness for implementing the Merdeka Curriculum.